(3GdeNJUQ aj Yde GdCKQs - (3YHO GdbGOQ Hf CHj GdhaG GdbQTjs
(3ChdgG (B:s
(3YfO GdCcKQ hGdJMbjb ggfG Cf jfXQ ai gPg GdeSFdI gd gi ef GdeSGFd GdJi jWdH ajgG GdLRe hGdjbjf Ch ef GdeSGFd GdJi jcai ajgG GdEbfGY s
(3BNQgG (B:s
(3hGdQeR HGdUdGI ecQhg cGf jcJH UdYe hjTjQ HPi Edi GdUdGI hGdSdGe aGdMb Cf jcJH HGdJeGe hdG jfbU ef fYhJ GdfHi Ydjg GdUdGI hGdSdGe hYdi Bdg hCUMGHg CLeYjf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf Je GdeNJUQ ai Yde GdCKQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdMOjK h GdeUWdMs